Cognitive Psychology Connecting Mind, Research, and Everyday Experience - Goldstein, E. Bruce, 1941- (Australia Wadsworth Cengage Learning, 2008)
Helps students understand the theories of cognition, driving home both the scientific importance of the theories and their relevance to students' daily lives. This title helps students gain an understanding of the behind the scenes' activity that happens in the mind when humans do such seemingly simple activities as perceive, remember, or think
Include Color Illustration, Glossary, Reference and Index
Keywords: Cognitive psychology -- Cognition -- Memory